Interpretive Structural Modeling Dalam Membangun Kebijakan Mitigasi Risiko Tambang : Pembelajaran Dari Koto Alam - Suci Mardiyah; Aldri Frinaldi; Rembrandt Rembrandt; Dasman Lanin (Jurnal Sains dan Ilmu Terapan, 2024)
This study aims to formulate mining risk mitigation policies in Nagari Koto Alam using the Interpretive Structural Modeling (ISM) approach. Nagari Koto Alam, located in Lima Puluh Kota Regency, faces significant challenges due to mining activities, including environmental degradation, landslides, and social conflicts. The ISM method is employed to analyze key elements influencing risk mitigation, such as government policies, community participation, and environmental management. Data were collected through literature reviews, field observations, and interviews with stakeholders, including local authorities, mining companies, and the local community. The results reveal that weak regulatory enforcement and insufficient reclamation efforts are the primary causes of risks. By mapping the relationships among elements hierarchically, this study identifies priority interventions, such as community education, stricter regulatory enforcement, and the implementation of sustainable mining practices. The recommendations provide a foundation for balancing economic benefits with environmental protection and community well-being.